The Serbian quality infrastructure as viewed by the quality managers - Ruso, Jelena Vidoje; Filipovic, Jovan; Rankovic, Biljana (Serbian Journal of Management, 2017)
Globalization of the modern society as well as the increased consumer awareness have lead to the situation where every country in the world has growing needs for a reliable Quality Infrastructure (QI). In this context, the paper highlights the importance of the development of Quality Infrastructure in Serbia in terms of institutional connectivity and legal regulation within the country. Operationally, the paper aims at examining the quality managers’ opinions about current situation of QI in Serbia, with the special emphasis on the National Quality Infrastructure (NQI) issues. Additionally, the article presents all governmental and other relevant organizations that may contribute to the development of QI model in Serbia as well as in the whole region, in economical, business and governmental surroundings. The results indicate that although NQI institutions are well established and regulated by the legislation of Republic of Serbia, there is still a room for improvement.